Youth Employment Strategies. Issue 2 (3rd March 2016) - Toreev, V.B.
Abstract : Research on the Russian labor market and how young Russians prepare for it shows that education is the main factor in their views of appropriate strategies for employment. Data also show that the education-to-work transition is hampered by a poor fit between the needs of the economy and the educational system.